A comparative sustainability evaluation of alternative configurations of an urban nitrogen removal solution targeting different pathways. (15th January 2023) - Pryce, David; Kapelan, Zoran; Memon, Fayyaz A.
Abstract: Limiting the introduction of excess nitrogen to natural water sources is a growing priority for water security and environmental health. This poses particular difficulties in urban environments where available land for potential solutions is limited. A promising option is the integrated fixed-film activated sludge (IFAS) process that requires only a small footprint and is capable of high total nitrogen (TN) removal through multiple pathways. In light of the sustainable development goals set out by the United Nations, the present work has sought to compare the sustainability of two TN removal pathways by comparing the technical, economic and environmental performance of their optimum configurations. Through modelling, a single-stage configuration demonstrated the capacity to achieve an effluent TN concentration of 8.7 mg/L by the simultaneous nitrification denitrification pathway when a dissolved oxygen concentration of 3.5 mg/L was provided. Addition of a post-anoxic stage at equal volume to the aerobic stage (1:1 aerobic to anoxic ratio) to target conventional nitrification denitrification could realise an effluent TN concentration of 4.2 mg/L when DO was increased to 4.5 mg/L, although 5.8 mg/L of effluent TN could be achieved with only a 5:1 ratio. In terms of environmental burden and economic costs, analysis of the system's life-cycle under these different configurations indicated considerable asymmetry of the two pathways during the operational phase due mainly to the increased aeration. However in spite of this, the two conventional configurations were ultimately both shown to be more sustainable than that of the simultaneous pathway due to the greater TN removal capacity afforded. Graphical abstract: Image 1 Highlights: Best configurations for nitrogen removal in bio-wastewater treatment identified. Sustainability assessed in terms of environment, economy and treatment performance. Higher performance but higher costs versus lesser performance but lesser costs. Conventional nitrification denitrification found to be most sustainable option. Treatment performance is critical aspect of sustainability.